Human papillomavirus association is the most important predictor for surgically treated patients with oropharyngeal cancer - Wagner, Steffen; Reuschenbach, Miriam; Prigge, Elena-Sophie; Knebel Doeberitz, Magnus von (British journal of cancer, 2017)
Background:Upfront surgery is a valuable treatment option for oropharyngeal squamous cell carcinoma (OPSCC) and risk stratification is emerging for treatment de-escalation in human papillomavirus (HPV)-related OPSCC. Available prognostic models are either based on selected, mainly non-surgically treated cohorts. Therefore, we investigated unselected OPSCC treated with predominantly upfront surgery.Methods:All patients diagnosed with OPSCC and treated with curative intent between 2000 and 2009 (n=359) were included. HPV association was determined by HPV-DNA detection and p16INK4a immunohistochemistry. Predictors with significant impact on overall survival (OS) in univariate analysis were included in recursive partitioning analysis.Results:Risk models generated from non-surgically treated patients showed low discrimination in our cohort. A new model developed for unselected patients predominantly treated with upfront surgery separates low-, intermediate- and high-risk patients with significant differences in 5-year OS (86%, 53% and 19%, P<0.001, respectively). HPV status is the most important parameter followed by T-stage in HPV-related and performance status in HPV-negative OPSCC. HPV status and ECOG remained important parameters in risk models for patients treated with or without surgery.Conclusions:Regardless of treatment strategies, HPV status is the strongest predictor of survival in unselected OPSCC patients. The proposed risk models are suitable to discriminate risk groups in unselected OPSCC patients treated with upfront surgery, which has substantial impact for design and interpretation of de-escalation trials.